Pengaruh Earning Per Share, Price Earning Ratio Dan Price To Book Value Terhadap Harga Saham Pada PT Bukit Asam Tbk Periode 2015 - 2024 - Dila Wulandari; Widya Intan Sari (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This study aims to examine the effect of earnings per share, price earning ratio, and price to book value on the share price of PT Bukit Asam Tbk for the period 2015–2024. The research population consists of PT Bukit Asam Tbk annual financial reports, with samples including financial position reports, income statements, notes to financial statements, and stock summaries for the period 2015–2024. analysis used descriptive statistics, classical assumption tests, multiple linear regression analysis, hypothesis testing, and the coefficient of determination with the help of SPSS ver 26. The results show a multiple linear regression analysis of Y = -6466.039 +7.757X1+587.412X2 + 923.166X3 + e. The coefficient of determination obtained was 79,6%, explaining the variation in Earnings Per Share, Price Earnings Ratio, and Price to Book Value against the Share Price. The t-test obtained Earnings Per Share t-count 4.768 > t-table 2.44691 and a sig 0.003 < 0.05, meaning Earnings Per Share partially affects stock prices. Price Earning Ratio tcount 3.120 > ttable 2.44691 with a sig 0.021 < 0.05, meaning Price Earning Ratio partially affects stock price. And Price to Book Value t-count 0.802 < t-table 2.44691 with a sig 0.453 > 0.05, meaning Price to Book Value does not partially affect stock prices. The F test Earnings Per Share, Price Earning Ratio, and Price To Book Value affect stock prices with Fcount 12.699 > Ftable 4.76 and a Sig 0.005 < 0.05